The Role of 'Financial Planning for Beginners' Seminar in Improving Financial Literacy and Planning for Beginners - Pahala, Indra; Eryanto, Henry; Rizan, Mohamad; Anwar, Choirul; Kresnamurti Rivai P, Agung; Zakiah, Rizka; Kurniati, Destria; Safitri, Gita; Ramadhanti, Nabila (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
In today's increasingly complex economic environment, the importance of financial literacy and effective financial planning has become paramount for individuals looking to secure their financial future. Financial literacy is closely linked to financial management, enabling individuals to understand key financial concepts, assess risks and manage their finances efficiently. This report examines the role of financial literacy in improving financial decision-making and planning, especially for beginners. By providing knowledge through the “Financial Planning for Beginners” seminar, organized by the Faculty of Economics of Universitas Negeri Jakarta in collaboration with the Indonesia Stock Exchange Gallery and Mirae Asset Sekuritas, we explore how such initiatives contribute to simplifying financial concepts for beginners. The seminar aims to enhance financial literacy, enabling participants to make informed financial decisions and plan effectively for a financially secure future. It also focuses on encouraging active engagement and learning through expert presentations and interactive Q&A sessions.